Essentials of performance analysis in sport - Second edition (Routledge, 2015)
This fully revised and updated second edition includes extended coverage of contemporary issues in performance analysis and incorporates the most recent developments in this quickly evolving field. It introduces the fundamental theory of match and performance analysis, using real-world illustrative examples and data throughout, and explores the applied contexts in which analysis can have a significant influence on performance.